2022
DOI: 10.1021/acsomega.1c05794
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Design of Cathode Materials for Na-Ion Batteries

Abstract: With the escalating demand for sustainable energy sources, the sodium-ion batteries (SIBs) appear as a pragmatic option to develop large energy storage grid applications in contrast to existing lithium-ion batteries (LIBs) owing to the availability of cheap sodium precursors. Nevertheless, the commercialization of SIBs has not been carried out so far due to the inefficacies of present electrode materials, particularly cathodes. Thus, from a future application perspective, this short review highlights the intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 42 publications
(25 reference statements)
0
57
0
Order By: Relevance
“…O3-type sodium layered oxides typically undergo various phase transitions during electrochemical (de)sodiation (e.g., O3-O'3-P3-P'3) and exhibit slow insertion kinetics at a high degree of sodiation (Gupta et al, 2022). Additionally, these materials are often prone to poor stability in humid atmospheres (Wang et al, 2018;Sun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…O3-type sodium layered oxides typically undergo various phase transitions during electrochemical (de)sodiation (e.g., O3-O'3-P3-P'3) and exhibit slow insertion kinetics at a high degree of sodiation (Gupta et al, 2022). Additionally, these materials are often prone to poor stability in humid atmospheres (Wang et al, 2018;Sun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To guide the design of Ca cathodes in this nascent technological field, much inspiration has been drawn from studies of Na-ion batteries due to the similarity in size between Na + and Ca 2+ ions (116 and 114 pm, respectively). Extensive Na-battery research has identified structures capable of accommodating large cations while simultaneously minimizing cathode strain during cycling, namely, layered materials with tunable basal spacing and/or open frameworks with large intercalant sites . Among potential candidates, Na super-ionic conductor (NaSICON) type materialssuch as Na 3 V 2 (PO 4 ) 3 (Na 3 VP) or Na 3 V 2 (PO 4 ) 2 F 3– y O y (NVPF)have been intensively investigated due to their promising cyclability, chemical tunability, and high discharge voltages. , These polyanionic frameworks boast remarkable structural stability as well as good ionic conductivity, and recent work has demonstrated their ability to reversibly host Ca 2+ ions with promising electrochemical performance. …”
Section: Introductionmentioning
confidence: 99%
“…Although a maximum of five transition metals containing P2‐type layered oxides have been reported, a recently discovered entropy and crystal‐facet modulated P2‐type Na 0.62 Mn 0.67 Ni 0.23 Cu 0.05 Mg 0.07 Ti 0.01 O 2 cathode has been able to deliver a long cycle life in half cell configurations (an 87% capacity retention after 500 cycles at 120 mA g −1 and about 75% capacity retention after 2000 cycles at 1.2 A g −1 ) 159 . Highly efficient Al 2 O 3 coating on the Na 0.67 Ni 0.33 Mn 0.67 O 2 particles enables enough surface modulation to mitigate the poor cycle life of the pristine cathode 139,160 . Additionally, composites of P2/P3 and P3/O3‐type cathode by modifying the sodium concentration have provided sufficient support to enhance the cycle life of the cells 130,161 .…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…159 Highly efficient Al 2 O 3 coating on the Na 0.67 Ni 0.33 Mn 0.67 O 2 particles enables enough surface modulation to mitigate the poor cycle life of the pristine cathode. 139,160 Additionally, composites of P2/P3 and P3/O3-type cathode by modifying the sodium concentration have provided sufficient support to enhance the cycle life of the cells. 130,161 Commercially, the second-generation FARADION battery utilizes a quadra-metal O3/P2-mixed-phase Ni-Mn-Mg-Ti system as the cathode.…”
Section: Current Trends and Commercial Prospects Of P2-type Naxtmo2 E...mentioning
confidence: 99%